Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Afinal, não é só Cabo Delgado! Dinâmicas da insurgência em Nampula e Niassa - Forquilha, Salvador; Pereira, João (IDeIAS, 2021)
Nos últimos três anos e meio, Moçambique enfrenta uma violência armada desencadeada por um grupo de natureza jihadista. Com origens na zona norte de Cabo Delgado e localmente conhecido pela designação Al-Shabaab, o grupo surgiu como uma seita religiosa (Morier-Genoud, 2020) e, de seguida, constituiu-se numa unidade militarizada, tendo partido para a violência armada a 5 de Outubro de 2017. Baseado em trabalho de campo nas províncias de Cabo Delgado, Nampula e Niassa, este texto procura analisar a insurgência com base em dinâmicas de alguns distritos de Nampula e Niassa. Com enfoque nos factores do avanço da insurgência no terreno, o texto sublinha o argumento, segundo o qual, a compreensão do desenvolvimento da insurgência em Cabo Delgado passa, entre outros aspectos, pela análise das dinâmicas sociais, económicas e religiosas das províncias vizinhas, nomeadamente Nampula e Niassa, que se transformaram em espaços férteis de recrutamento, particularmente a partir de 2018. O argumento é desenvolvido em dois momentos. No primeiro momento, o texto procura identificar e analisar os principais factores que conduziram ao alastramento da insurgência para mais distritos de Cabo Delgado e à tentativa de instalação de células de tendência radical em alguns distritos de Nampula e Niassa. No segundo momento, focaliza-se a atenção para as dinâmicas de recrutamento a nível interno, com destaque para alguns distritos localizados na zona costeira de Nampula e na fronteira entre a província de Niassa e a Tanzânia.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Estabelecimento Da Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) Nas Províncias de Tete, Gaza, Nampula - RMDDH (CDD - Centro para Democracia e Desenvolvimento Mozambique, 2021)
A Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) está a levar a cabo actividades de identificação e mapeamento de defensores de direitos humanos nas províncias, que incluem pessoas singulares e organizações da sociedade civil que estão na linha de frente na luta pela defesa dos direitos humanos. Financiado pela OCISA, o trabalho iniciou em Abril último na Província de Tete, centro de Moçambique, onde a RMDDH realizou vários encontros com organizações da sociedade civil que trabalham na área dos direitos humanos e com instituições governamentais e estatais
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Gaza; GP - Nampula; GP - Tete; L - portuguese / português; civil society / sociedade civil

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Jovens moçambicanos descontentes com falta de oportunidades (DW.COM, 2020)
No Dia Mundial da Juventude, jovens da província moçambicana de Nampula queixam-se da falta de emprego, de habitação e de acesso ao crédito financeiro. O novo coronavírus também é um dos maiores problemas atualmente.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; employment / emprego; youth / juventude

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Investimento Directo Estrangeiro e o Desenvolvimento Socioeconómico em Moçambique: Dinâmicas, Tensões e Desafios - Sambo, Michael Godet (Desafios para Moçambique 2020, 2020)
Considerando a estrutura económica de Moçambique e analisando a estrutura do IDE que aflui a Moçambique, este artigo argumenta que o aumento de IDE na economia não é necessariamente a condição para o desenvolvimento se não for maximizada a captação e utilização das receitas. Embora a lógica de fomento do desenvolvimento económico através do investimento adoptada pelo Governo de Moçambique no PQG 2015-2019 tenha um embasamento teórico, o seu enquadramento é simplista e pouco considera a natureza do investimento, o contexto em que este é aplicado e o seu efeito estrutural na economia. O argumento resulta, além da revisão bibliográfica e documental, de uma análise dos dados económicos oficiais de Moçambique, com destaque para os dados do IDE publicados pelo Banco de Moçambique, conjugados com a análise dos materiais de trabalhos de campo sobre o IDE na província de Nampula em 2016 e na Província de Gaza em 2019. O texto está estruturado em três partes além da introdução e conclusão. A primeira faz um enquadramento teórico da discussão, a segunda analisa as dinâmicas de IDE na economia e a terceira analisa algumas evidências empíricas dos efeitos socioeconómicos causados pelos projectos de IDE nas comunidades receptoras dos projectos.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Cadernos IESE, 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Coesão social e violência política em Moçambique: notas para debate - Forquilha, Salvador; Gonçalves, Euclides (Conferência do IESE – “Desafios para Moçambique: Dez anos pensando o país”, 2019)
Perguntas e método de pesquisa Contexto: • Dados da primeira fase de uma pesquisa programática no norte de Moçambique Pergunta: • Como operacionalizar operacionalizar a noção de coesão social em Moçambique? • Que subsídios a noção de coesão social pode oferecer para a compreensão da violência política em Moçambique? Recolha de dados • Período: Abril e Maio de 2019 • Locais: Cidade de Maputo, Chiúre (Cabo Delgado), Chimbunila (Niassa) e Mussuril (Nampula) • Entrevistas: Representantes e membros de partidos políticos, líderes comunitários e religiosos, grupos de camponeses e jovens • Análise de dados: Mapeamento de factores com potencial para conflicto (conflict mapping)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

O processo de empoderamento das raparigas em Marrere - Estudo de caso do Projeto Mwarusi - Eloisa Nair Lopes da Costa (Instituto Universitário de Lisboa, 2018)
Desde o Acordo Geral de Paz, assinado em 1992, Moçambique realizou reformas políticas de intervenção no combate à pobreza. Contudo, em 2006, verificou-se que 54% da população moçambicana ainda se encontrava abaixo da linha de pobreza. Foi então que, Moçambique, em parceria com organizações internacionais iniciou os seus esforços na promoção de programas centrados na igualdade e equidade de género e a sua atuação junto de comunidades mais vulneráveis, tendo em conta particularmente a educação e a saúde. Para estes avanços contribuíram os Objetivos de Desenvolvimento do Milénio e o Plano de Ação para a redução da pobreza absoluta. O estudo de caso desenvolvido nesta dissertação tem como objetivo compreender o modo pelo qual o Projeto Mwarusi, implementado pela Girl Move Foundation, contribui para um empoderamento efetivo das raparigas no bairro de Marrere em Nampula, Moçambique, compreender o seu impacto na comunidade e a sua aplicabilidade a outras comunidades e grupos. Para compreender o Projeto Mwarusi e, em particular, a situação da mulher moçambicana e as políticas de promoção de igualdade, equidade e empoderamento existentes em Moçambique, foi necessário realizar-se uma análise multivariada que nos permitiu obter um conhecimento não só teórico, ao nível das perspetivas em questão, como prático que nos deu a oportunidade de conhecer a comunidade, a sua cultura e as suas tradições. Esta investigação tem, então, como objetivo a análise do Projeto Mwarusi, através de uma observação participante ao longo das sessões do projeto, através da realização de entrevistas semiestruturadas e questionários on-line aplicados a seis guias, a oito mentoras do Projeto Mwarusi, o que nos permitirá avaliar o sucesso e impacto do Projeto Mwarusi e, por último, através do acompanhamento do desenvolvimento do projeto entre 2015 e 2018.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; empowerment / empoderamento; gender / género; youth / juventude

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Elite Bargains and Political Deals Project: Mozambique Case Study - Vines, Alex (UK Government Stabilisation Unit, 2018)
This case study is one of a series commissioned to support the Stabilisation Unit’s (SU) development of an evidence base relating to elite bargains and political deals. The project explores how national and international interventions have and have not been effective in fostering and sustaining political deals and elite bargains; and whether or not these political deals and elite bargains have helped reduce violence, increased local, regional and national stability and contributed to the strengthening of the relevant political settlement. Drawing on the case studies, the SU has developed a series of summary papers that bring together the project’s key findings and will underpin the revision of the existing ‘UK Approach to Stabilisation’ (2014) paper. The project also contributes to the SU’s growing engagement and expertise in this area and provides a comprehensive analytical resource for those inside and outside government
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; decentralization / descentralização; electoral geography / geografia eleitoral

Empregados do Quintal (male domestic workers) in Nampula City: Domestic work, masculinities and matrilinearity - Humbane, Jossias Helder Jamisse (2018)
This study questions why domestic work that is generally considered a feminine job is yet a field dominated by men in the city of Nampula, Mozambique. In the attempt to explain this phenomenon, the research explores economic, social and cultural aspects. Due to the fact that Nampula is a province with a strong Islamic presence and the majority of the population identify themselves as belonging to the Makhuwa ethnic group—which is traditionally defined by a matrilinear kinship system—I argue that the domestic sector remaines masculinised because of the influence of the matrilinear values and gendered practices. I also argue that the Islamic patriarchal values play a decisive role as men see themselves as the exclusive family providers and for that reason forbid their wives to develop and to get engaged in economic activities outside the household. This study also explores notions of masculinity in connection with domestic work and examines how male domestic workers, coming from rural areas and employed in the city, perceive and perform their masculine identities. How does the job of the domestic worker shape particular understandings of masculinity? Given the fact that many domestic workers in Nampula are immigrant people from the rural areas of the Zambézia province, I argue that migrating and working in the city is considered as a way to achieve a manhood as immigrants have access to goods that can only be purchased in urban contexts and are scarce in the villages. The access to all these “modern” commodities and the experience of the city make the immigrant young boys to gain respect in their original communities.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; employment / emprego; gender / género

An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

O agronegócio no desenvolvimento do meio rural em Moçambique: perceção e análise das cadeias de valor de milho e da mandioca na província de Nampula - Linha, Paulo (Universidade de Lisboa, 2017)
O Agronegócio em Moçambique poderá ser um factor dinamizador da agricultura, chave para o desevolvimento económico, elemento para a equidade no desenvolvimento social e fundamental para a redução da pobreza e da fome. O estudo analisa as perceções dos atores do agronegócio do milho e da mandioca sobre o impacto destas culturas na vida económica e social no meio rural. Diante desta perspetiva, esta pesquisa teve como objetivo investigar prospectivamente as cadeias de valor das culturas do milho e da mandioca, no corredor de Nacala, com vista a identificar formas de potenciar o desenvolvimento do agronegócio como fator dinamizador da promoção do desenvolvimento socioeconómico sustentável no meio rural. Os resultados alcançados indicam que em Moçambique, de forma geral, o agronegócio do milho e da mandioca é potencial pilar dinamizador que poderá contribuir para o desenvolvimento da agricultura e impulsionar o crescimento económico e o desenvolvimento social se o Estado colocar-se na dianteira na criação, nas zonas de produção, de infraestruturas públicas para a prática de uma agricultura economicamente sustentável e uma legislação flexível e promotora de um clima propício para o agronegócio. Com as infraestruturas públicas criadas nos centros de produção deve-se optar, pelo envolvimento de todos atores do agronegócio num sistema de Integração e Coordenação Vertical, apostando na transformação da baixa renda da agricultura rural em agricultura comercial e competitiva para que efetivamente o agronegócio seja um dos pilares para o combate da fome e da pobreza no meio rural. A Integração e Coordenação Vertical, significa a existência de instituições âncoras que se dedicam a puxar a atividade do agronegócio dos produtores locais na base contratual. Esta forma promete rápida integração ao mercado, crescimento económico, inovação tecnológica, ao mesmo tempo em que protege os direitos e a autonomia do produtor sob regime de integração e coordenação. Agribusiness in Mozambique could be a driving force for agriculture, key to economic development, an element for equity in social development and fundamental to reducing poverty and hunger. The study analyzes the perceptions of corn and cassava agribusiness actors on the impact of these crops on economic and social life in rural areas. The objective of this research was to investigate prospectively the corn and cassava value chains in the Nacala corridor in order to identify ways to promote the development of agribusiness as a driving force for the promotion of sustainable socioeconomic development in the environment rural. The results indicate that, in general, corn and cassava agribusiness in Mozambique are potential pivotal factors that could contribute to the development of agriculture and boost economic growth and social development, if the government takes the initiative to build public infrastructures for an economic sustainable agriculture as well as create a flexible legislation that promotes a proper environment for agribusiness. With the public infrastructures created in the production centers, one must opt for the involvement of all agribusiness actors in a system of Integration and Vertical Coordination, betting on the transformation of low income from rural agriculture into commercial and competitive agriculture so that agribusiness is effectively a pillar to combat hunger and poverty in rural areas. Integration and Vertical Coordination means the existence of anchor institution dedicated to pull the agribusiness activity of the local producers in the contractual basis. This form promises rapid market integration, economic growth, technological innovation, while protecting the rights and autonomy of the producer under integration and coordination.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; agriculture / agricultura; private sector / setor privado

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Relatório Final da Pesquisa sobre o Impacto da Descentralização dos Fundos Sectoriais de Estradas, Águas e de Construção Acelerada de Salas de Aulas nas Províncias, nos Distritos e nas Autarquias Locais - Kulipossa, Fidelx Pius; Nguenha, Eduardo Jossias (The Open University consultancy, 2009)
A 17a Sessão Ordinária do Conselho de Ministros realizada em 2007 tomou a corajosa decisão de descentralizar os fundos dos sectores de estradas, águas, agricultura, e infra-estruturas de educação e saúde para garantir a implementação efectiva da Lei 8/2003 sobre os Órgãos Locais do Estado e materializar os objectivos estratégicos definidos no PARPA II e no Plano Quinquenal do Governo. Tal decisão, em parte, reconhece que a pobreza absoluta que flagela muitos cidadãos está estreitamente ligada à falta de acesso aos serviços básicos tais estradas, água potável, infra-estruturas escolares e de saúde e outros serviços úteis para a sobrevivência e sustentabilidade da vida humana. Com efeito, presumia-se que ao se descentralizar estes fundos sectoriais para os níveis provinciais e distritais, as instituições locais teriam maior capacidade de resposta às demandas da população em termos de prestação de melhores serviços, de maneira que ela estivesse mais satisfeita e participasse activamente na vida política e económica do país. Em termos de produção legislativa, regista-se avanço significativo na descentralização de fundos sectoriais. Porém, sendo essa legislação muito recente e em fase primária de sua implementação, constatam-se algumas reservas na implementação efectiva da mesma. Por exemplo, os progressos sectoriais na descentralização de fundos são diferenciados. No sector de estradas, os fundos são geridas e os pagamentos efectuados a partir do nível central através da Administração Nacional de Estradas (ANE). Relativamente aos sectores de água e de educação (construção acelerada de salas de aulas) os fundos são geridos a nível provincial e os pagamentos feitos nos dois níveis: provincial e distrital. A leitura do processo, e com respeito às constatações feitas nas províncias de Nampula e Gaza, onde decorreu o trabalho de campo, revelou diferenças peculiares nos avanços e na forma de abordagem da descentralização nas duas províncias, particularmente nos aspectos referentes a critérios de planificação, definição de prioridades, alocação de recursos e fluxos financeiros. As diferenças verificadas para as duas províncias, que podem ser explicadas, em parte, pela diferença de maturidade na condução dos processos de descentralização entre Nampula e Gaza, sendo a primeira mais experiente, não inibem concluir que, em termos gerais: (1) a descentralização de fundos sectoriais ainda não é efectiva; (2) o envolvimento das instituições de planificação e consulta comunitária é efectivo; (3) o sistema de prestação de contas é complexo, moroso e contraproducente; (4) o sistema de monitoria e avaliação ao nível distrital pode ainda ser melhorado; (5) a capacidade de manutenção ao nível distrital precisa de fortalecimento; (6) há fraco envolvimento do sector privado na prestação de alguns serviços; (7) há desarticulação institucional na aplicação de alguma legislação; (8) os critérios de atribuição de fundos sectoriais são inconsistentes e pouco divulgados; e (9) há, nos distritos, falta de uma perspectiva multisectorial e sistemática de planificação. Face aos problemas identificados, este Relatório Final propõe algumas recomendações: nova abordagem sobre os fundos sectoriais, particularmente a sua integração nos PESOD; alinhamento dos instrumentos de planificação estratégicos locais com os nacionais; regulação em legislação própria dos critérios de alocação de fundos, capacitação institucional entre outras acções.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; education / educação; infrastructure - roads / infrastructura - estradas

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Sex, Food and Female Power: Discussion of Data Material from Northern Mozambique - Arnfred, Signe (Sexualities, 2007)
Issues of sex and food are often inscribed in male/female relationships. Frequently in a western context sex is perceived as a site of male power and female subordination, while food and cooking are seen as female domains, but still sites of subordination, as elements of women's household chores. In this article, looking at issues of sex and food in a rural matrilineal setting, power aspects of male/female relationships as mediated through sex and food emerge somewhat differently. Sexual proficiency is here a woman's art, mastered by old women and transmitted to the young. Also, in a setting where daily life is largely based on subsistence production, food and cooking become domains of power, again with old women in control. Based on fieldwork in northern Mozambique and with reference to African feminist conceptualizations of male/female power relationships, the article makes a case for rurality and ‘tradition’ not necessarily being adverse to female power in social relationships.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; gender / género; youth / juventude

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

From ‘Abaixo’ to ‘chiefs of production’: Agrarian change in Nampula province, mozambique, 1975–87 - Dinerman, Alice (The Journal of Peasant Studies, 2001)
This article reconstructs key aspects of the evolving relationship between state institutions and former regulos (Portuguese‐appointed chiefs), in Nampula Province, Mozambique during the first 12 years of independence. In doing so, it simultaneously draws on and critiques two opposing interpretations of revolution and counterrevolution which have dominated scholarly production on post‐independence Mozambique and have polarized Mozambican studies in recent years. Against both sets of literature, my study finds that state socialism did not always and everywhere bring major disruptions to grassroots structures of authority; rather, many families who had been recognized by the Portuguese as royals were able, through a variety of strategies, to maintain their grip on local power. Secondly, I argue that the provincial government's enlistment of former regulos to serve as ‘chiefs of production’ was but one aspect of an attempt on the part of officialdom to recreate the most salient aspects of the colonial cotton regime rather than a war‐induced genuflection by the Frelimo regime to Renamo on the question of chiefly rule, as has been claimed by what I call ‘revisionist’ scholarship. Frelimo's refusal to acknowledge the role of villagization in agricultural decline throughout the country, a point raised and highlighted by revisionist writing is, however, crucial to understanding the ideological practices that helped justify and legitimate the return to Portuguese precedent on matters relating to rural labour. The reasons why Nampula was the site of these initiatives are explored.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; agriculture / agricultura; authority / autoridade